Pengembangan Aplikasi Holiyay untuk Perencanaan Liburan Sesuai Anggaran - Natanael Yohanes Gunawan; Hansen Gunawan; Ivan Cornelius Saputra; Putu Crysta Lovita Atmaja; Cynthia Antoni; Lifia Yola Febrianti (Fakultas Teknik Universitas Cenderawasih, 2023)
Many people aspire to go on vacations, but their wishes often go unfulfilled due to the difficulty of managing the required budget for the trip. Additionally, they encounter challenges in selecting a holiday destination because well-known tourist spots tend to be crowded with visitors, leading to a less comfortable experience. These issues have sparked the interest of a research team in developing an application to address these concerns. The application is designed based on feedback obtained from a survey conducted by the research team. After processing and analyzing the survey results, the team has conceptualized an application called